Tinjauan Hukum Terhadap Kebijakan Data Pribadi Konsumen Dalam Transaksi E- Commerce - Haidi, Nasrul; Gunawan, Yusuf (Neolectura, 2025)
This study aims to examine the legal protection of consumer personal data in e-commerce transactions and evaluate the legal responsibility of marketplace platforms in the event of data breaches. The focus lies in understanding the forms of legal safeguards based on Indonesian data protection laws and the obligations of digital platforms when consumer data is leaked. A normative juridical approach is used, supported by descriptive qualitative analysis, based on literature studies and data breach cases from e-commerce companies in Indonesia. The findings show that although regulations such as Law No.27 of 2022 on Personal Data Protection and the. Electronic Information and Transactions Law exist, enforcement remains weak. Key challenges include lack of supervision,limited awareness among business actors,and. inadequate law enforcement. This research recommends strengthening regulations, establishing effective supervisory systems, and enforcing strict penalties to ensure consumer data is protected and digital transactions can operate with in asecure legal framework.